Perception of Sustainability Reporting – an Attempt by Means of Eye-Tracking - Thorsten Litfin; Gunther Meeh-Bunse; Katja Luer; Özlem Teckert (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Financial reporting–going back to the work of the Croatian Benedikt Kotruljević in 1458 - has been significantly developed in recent years. Notwithstanding this, financial reporting is no longer perceived as comprehensive. Large public-interest preparers as well as their suppliers have been facing pressure in their reporting: Only financial reporting together with nonfinancial reporting on Corporate Social Responsibility (CSR) is said to achieve a comprehensive view of a company's performance. Such reporting discloses amongst others social and environmental matters e.g. by means of a sustainability report. However, as there are different reporting types the goal of this paper is to identify the superior CSR reporting type from a stakeholder's perspective. After identifying and analyzing central guidelines on CSR reporting and presenting different approaches, the authors will apply positive-empirical methodology by using Eye-Tracking technology. In this first innovative joint attempt for approaching CSR quality by Eye-Tracking technology students act as subjects in order to develop hypothesis for future research after feedback from conference participants
Keywords: M14; M48; 330; sustainability reporting; quality; eye-tracking; stakeholder perception